ChemInform Abstract: Quinoline and Phenanthroline Preparation Starting from Glycerol via Improved Microwave‐Assisted Modified Skraup Reaction. Issue 2 (January 2015) - Saggadi, Hanen; Luart, Denis; Thiebault, Nicolas; Polaert, Isabelle; Estel, Lionel; Len, C.
Abstract Microwave‐assisted modified Skraup reaction of anilines with glycerol provides access to quinoline derivatives.